Increasing science process skills using student worksheet guided inquiry-based learning on a simple plane of materials - Afrizal Satya Hadi; Wahono Widodo (Jurnal Pijar Mipa, 2022)
The study aimed to describe the impact of guided inquiry-based student worksheets on improving the scientific process skills in simple machine materials. This research method uses pre-experimental with the design of one group pretest and posttest. The research targeted samples were students in grade eight junior high schools, 40 Surabaya, Indonesia. The data was obtained by experimental methods with an instrument learning plan, student worksheet, learning implementation sheet, pretest and posttest sheet, and student response questionnaire analyzed in quantitative descriptions. The study results showed that the implementation of learning during two meetings got an average of very good and practical criteria. The target skills are the science process involved in formulating problems, identifying variables, hypothesizing, experimenting, analyzing, concluding, and communicating data. An improvement occurs in professional, scientific process skills. The average N-Gain value obtained 0,75 from the pretest and posttest, categorized as high and effective. The students gave an 88.8% response which was categorized as very good. In conclusion, learning by using guided inquiry-based student works can improve science process skills on simple machine materials.